LOYALITAS PELANGGAN BERBASIS WORD OF MOUTH, BRAND IMAGE DAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING - Gemina, Dwi; Rahmawati, Dewi; Kartini, Tini (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.08.TAHUN.2024DO - 10.24843/EEB.2024.v13.i08.p20, 2024)
Customer loyalty arises when customers exhibit strong interest leading to repeat purchases. Marketing strategies aimed at maintaining product superiority over competitors involve efforts to enhance customer satisfaction. This study aims to analyze the direct, indirect, and overall impacts of word of mouth and brand perception on customer loyalty through customer satisfaction. The research focused on loyal customers of S-26 Ultima milk products from PT. Nestle Indonesia in Bogor City, with a sample of 100 individuals selected through proportional random sampling. Analytical methods included descriptive analysis, validity and reliability testing, classical assumption verification, path analysis, and the Sobel Test for mediation analysis. Findings indicate that both word of mouth and brand image significantly and directly contribute to customer satisfaction. Moreover, word of mouth, brand image, and customer satisfaction collectively influence customer loyalty positively. Additionally, word of mouth and brand image indirectly enhance customer loyalty through customer satisfaction. The implication of these findings is that PT Nestlé Indonesia is recommended to regularly conduct satisfaction surveys and offer special warranties to increase customer loyalty. In addition, the company needs to create a strong emotional experience and match the product price with the quality to improve the brand image and word of mouth of S-26 Ultima products.